The Novel CFTR Mutation A457P in a Male with a Delayed Diagnosis of Cystic Fibrosis - Kate H. Cole; Patrick R. Sosnay; Lonny B. Yarmus; Jonathan B. Zuckerman (Case Reports in Medicine)
Cystic fibrosis (CF) is an autosomal recessive disease that may be caused by more than 1000 different mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. We describe the case of a CF patient who was initially diagnosed at 16 years of age after presenting with mild respiratory compromise and pancreatic sufficiency. When genetic testing was first performed using a CF mutation panel, only a single F508del CFTR allele was identified. We subsequently performed testing, which revealed a previously unreported mutation: A457P (p.Ala457Pro, c.1369G>C). The patient's clinical course through adulthood is described, and genotype-phenotype correlation is discussed. The A457P mutation appears to confer a relatively mild phenotype, as is usually observed with CFTR class IV–VI defects. With the advent of more comprehensive and widely available genetic testing techniques, identification of CF genotypes in patients with milder disease variants may help stratify patients for targeted therapy and prevent late complications of the disease.